Combination of Irisin, Uric Acid, and Pro-Inflammatory Cytokine To Distinguish Gout Patients From Healthy Controls in The Governorate of Thi-Qar - Kareema A. Dakhil; Manal A. Aziz; Wajdy J. Majid (Academia Open, 2023)
This study aimed to investigate the potential of combining uric acid levels with pro-inflammatory cytokines, specifically interleukin-1β (IL-1β) and the myokine irisin, to enhance the precision of gout diagnosis. The patient group comprised 80 individuals with gout, while the control group included 70 healthy subjects. Serum levels of IL-1β and irisin were measured in both groups, and Pearson correlation analysis was employed to assess their relationships with serum uric acid. Results revealed that gout patients exhibited significantly higher levels of IL-1β and serum uric acid but lower irisin levels compared to the control group. Negative correlations were observed between irisin and IL-1β, as well as between irisin and uric acid. Conversely, a positive correlation was found between serum uric acid and IL-1β. Receiver operating characteristic (ROC) curve analysis demonstrated high diagnostic accuracy for both IL-1β and irisin in discriminating gout patients from healthy individuals, suggesting their potential utility as diagnostic indicators for gout. This study underscores the promise of combining IL-1β, irisin, and uric acid measurements to enhance the accuracy of gout diagnosis, paving the way for further multicenter trials to validate this approach's effectiveness. Highlights: Novel Diagnostic Approach: This study proposes a novel diagnostic approach for gout by combining serum levels of uric acid with pro-inflammatory cytokines IL-1β and myokine irisin, demonstrating its potential to enhance precision. Correlation Insights: The study reveals significant correlations between uric acid, IL-1β, and irisin levels, shedding light on the intricate relationship between inflammation, myokines, and gout pathophysiology. Diagnostic Accuracy: High diagnostic accuracy, as indicated by ROC curve analysis, underscores the clinical utility of IL-1β and irisin as potential indicators for gout diagnosis, offering a promising avenue for improved clinical assessment. Keywords: Gout Diagnosis, Interleukin-1β, Irisin, Uric Acid, Pro-Inflammatory Cytokines.